A novel period-based method for the measurement direct current motor velocity using low-resolver encoder - Top, Ahmet; Gokbulut, Muammer (Sage Publications Ltd, 2023)
Direct current (DC) motors-which have widespread usage areas such as industrial devices, automobiles, and household appliances-are also widely used in robotic systems that have developed rapidly in recent years and need precise control. Since the DC motors with encoder on its shaft used in robots have low resolution, accurate speed measurement cannot be made and this makes robot control difficult. In this study, a novel period-based measurement approach is presented to more accuracy and precision determine DC motor velocity at high speed with signals obtained from a low-resolver incremental encoder. First, the signals of the dual channel encoder are applied to the exclusive or gate to produce a single output signal with twice the frequency in order to reduce the number of interrupt pins used in the microcontroller and optimize the program cycle time. Based on the sample count calculated with the entered by user reference speed and microcontroller loop time, the mean filter is then applied to the half-wave period of the signal received through the Arduino board interrupt pin. In order to demonstrate the effectiveness of the method, measurement made with three different methods as follows: traditional period-based method, half-wave period method with only one channel, and exclusive or output signal half-wave period method. The results show the high-speed measurements through the presented method outperform other methods at high DC motor speeds. Especially in robots using more than one motor, the processing load of microcontroller has reduced and enabled the use of other peripheral interfaces by reducing the number of microcontroller pins used for the encoder. In addition, utilizing the results obtained with this method, the proportional-integral-derivative (PID) control of the motors in a four-wheel drive mobile robot is carried out for different speeds.
Keywords: Optic incremental encoder; PID; DC motor; period-based method